Routledge handbook of religion and ecology - Jenkins, Willis; Tucker, Mary Evelyn; Grim, John (Routledge international handbooks, 2018)
"The Routledge Handbook of Religion and Ecology provides the most comprehensive and authoritative overview of the field. Written by a team of leading international experts, the Handbook discusses dynamics of change within religious traditions as well as their roles in responding to global challenges such as climate change, water, conservation, food and population. It explores the interpretations of indigenous traditions regarding modern environmental problems drawing on such concepts as lifeway and indigenous knowledge. This volume uniquely intersects the field of religion and ecology with new directions within the humanities and the sciences. The sections on environmental humanities and environmental sciences explore the history and significance of other key areas and disciplines of environmental studies in which religion and ecology can be fruitfully located as a dialogue partner for environmental solutions"--